CHEMICAL AND PHYSICAL PROPERTIES OF KLUWAK (Pangium edule Reinw.) SEED OIL - , Widelia Ika Putri, Dr. Ir. Supriyanto, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Kluwak (Pangium edule Reinw) seed is rich in oil. On the other hand, there is increasing of vegetable oilâs demand in the world continuously. This is a chance to develop kluwak seed as vegetable oil source. Every commercial product has its specification